Korean Drama Reputation Among Indigenous Students in Kochi, Kerala - Bagait, Vishakha Sandeep; Babu, Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Korean Drama (K Drama) is popularly known for its beauty and quality. Student communities in all countries prefer viewing Korean contents extensively. The Computerization and Internationalization phenomenon have contributed to the availability of variety internet data packaging in business. Irrespective of age, profession and income people got a chance to utilise the online services from different service providers. It had enhanced the trend of viewing foreign media contents. Korean media became prominent in India through entertainment programs. As the simplicity, content and quality standards of K Drama were outstanding, it became immensely famous among the Indian student groups. Present study is an endeavour to find the factors that made the Korean media famous among students in the Kochi, India. India is significantly impacted with the festive fever of wave- KoreanTV shows. Research data states that Indian students practice ‘media diet’ which is the addiction to a TV program towards the K Dramas. K Drama is familiar among students, as it is available on various internet platforms like via Netflix, Amazon Prime, etc. Digitalisation and availability of internet free subscription with subtitles in English has engaged them to stick on the monitors for longer periods.